TEACHERS’ PEDAGOGIC COMPETENCE AT SD NEGERI 168 PEKANBARU - Ayu Puspitaningsari; Zufriady Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The purpose of this research was to describe the teachers’ pedagogic competence at Sekolah dasar Negeri 168 Pekanbaru. This research was conducted on July 2020. The type of this research was quantitative which provided the description about the current condition on the research object which was the teachers’ pedagogic competence at Sekolah dasar Negeri 168 Pekanbaru. The sampling techniques applied in this research was a saturated sampling. The samples of this research were all teachers of ekolah dasar Negeri 168 Pekanbaru amounted 15 teachers. Data were collected through a 71-items questionnaire via google form with the instrument of a positive and negative statement about teachers’ pedagogic competence with four alternative answers. The research results concluded that the teachers’ pedagogic competence at Sekolah dasar Negeri 168 Pekanbaru reached 87.62% with “Very Good” category. The number of core competency who scored in the interval 85-100 with the category of